Two populations of less-virulent Helicobacter pylori genotypes in Bangladesh. - Hafeza Aftab; Muhammad Miftahussurur; Phawinee Subsomwong; Faruque Ahmed; A K Azad Khan; Takashi Matsumoto; Rumiko Suzuki; Yoshio Yamaoka (PLoS ONE)
Bangladesh has a population with a low gastric cancer risk but high prevalence of Helicobacter pylori infection. Several studies have examined virulence genes in H. pylori from Bangladesh. We analyzed cagA and vacA subtypes and their association with severe histology phenotypes, and analyzed population types among Bangladeshi strains. We included patients who underwent endoscopy in Dhaka. Sequences of virulence genes and seven housekeeping genes were obtained by next generation sequencing and confirmed by Sanger sequencing. We isolated 56 H. pylori strains from 133 patients, of which 73.2% carried cagA, and all were considered Western-type. Patients infected with cagA-positive strains had more severe histological scores than patients infected with cagA-negative strains. Among vacA s1 and m1 genotypes, the s1a (97.8%, 43/44) and m1c (28/30, 93.3%) genotypes were predominant. All strains containing s1 and m1 (30/56, 53.6%) also had i1, d1, and c1. In contrast, all strains containing the less-virulent genotypes s2 and m2 (12/56, 21.4%) also possessed i2, d2, and c2. Multivariate analysis indicated that subjects infected with vacA m1-genotype strains only had a significantly higher risk of antrum atrophy than patients infected with m2-genotype strains. Of the two main H. pylori populations in this study, hpAsia2 strains were associated with higher activity and inflammation in the antrum compared to hpEurope strains; however, only vacA s1m1i1d1c1 strains, independent of population type, were significantly associated with inflammation in the antrum, unlike the s2m2i2d2c2 genotype. In conclusion, Bangladeshi strains were divided into two main populations of different genotypes. The low incidence of gastric cancer in Bangladesh might be attributable to the high proportion of less-virulent genotypes, which may be a better predictor of gastric cancer risk than the ancestral origin of the H. pylori strains. Finally, the vacA m region may be a better virulence marker than other regions.